Gestión de proyectos ambientales en la industria de la hospitalidad en Rusia utilizando el criterio "riesgo-rentancia" - Kovaltchuk, Andrey P.; Miloradov, Konstantin A.; Nikolskaya, Elena Y.; Gunare, Marina L. (Revista de Investigaciones Universidad del Quindío, 2022)
The article describes the approach proposed by the authors to analyze the effectiveness of projects for the introduction of eco-technologies in hotels concerning the risk-return ratio. The net present value (NPV) of the project is used as a criterion for assessing the profitability of the green technology implementation project. The magnitude of the project risk is the second criterion, which can be calculated by various methods. Applying the proposed approach, the authors analyzed the experience of implementing environmental projects by Russian hotels. An illustration of the proposed method is the 'risk-return' diagram for introducing energy-saving technologies in a 3* hotel. The approach combines the advantages of the analysis method for discounted cash flow project efficiency and project risk analysis tools by using two criteria and can be applied for a quick and visual analysis of environmental projects in the hospitality sector.